Comparison of Formal and Informal Structures in Organizations Using the Social Network Analysis - Seyedeh Motahareh Hosseini; Mohammad Aghdasi (مدیریت صنعتی)
Objective Organizational structures are purposefully crafted around the strategic objectives of companies, incorporating well-defined processes that serve as the foundation for employee activities and communication. The processes and activities of organizations and companies are implemented through organizational roles and positions that are assigned to employees based on the structure and goals. However, the crucial question lies in how effectively official structures can address people's communication needs and facilitate the implementation of activities. Within numerous organizations, an informal structure emerges in parallel to the official hierarchy, leading to the execution of various activities based on the relationships established within this informal framework. Because of various reasons, employees in some organizations are forced to carry out organizational processes through informal communication and in temporary work teams. The presence of an informal structure in numerous organizations is an unavoidable phenomenon. However, the primary concern lies in effectively monitoring and appropriately managing this structure and the relationships that arise from it. This study mainly seeks to measure the degree of similarity and difference between the formal and informal structures of the organization.